(3GdeDJda hGdeNJdas - (3CHh eMeO YHO GdZfj Hf SYjO GdMGaX, GdGROj GdeUQj,J (B409 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg CKfGA (B( (3HGH CSjO HGdaJM (B) (3Hbhdg (B: (3GSjO Hf CSjO GdSGYOi Yf CHjg s
(3BNQgG (B:s
(3jfJgi CKfGA (B( (3HGH Ydi hYdi hBNQ eG ajg (B: (3hYdi HVe GdYjf hJTOjO GdjGA (B: (3gh Ydi Hf QHGM , hGdOehSi Hf Ydi s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B33s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs